Purification of time-resolved insulin granules reveals proteomic and lipidomic changes during granule aging - Martin Neukam; Pia Sala; Andreas-David Brunner; Katharina Ganß; Alessandra Palladini; Michal Grzybek; Oleksandra Topcheva; Jovana Vasiljević; Johannes Broichhagen; Kai Johnsson; Thomas Kurth; Matthias Mann; et al. (Cell Reports, 2024)
Summary: Endocrine cells employ regulated exocytosis of secretory granules to secrete hormones and neurotransmitters. Secretory granule exocytosis depends on spatiotemporal variables such as proximity to the plasma membrane and age, with newly generated granules being preferentially released. Despite recent advances, we lack a comprehensive view of the molecular composition of insulin granules and associated changes over their lifetime. Here, we report a strategy for the purification of insulin secretory granules of distinct age from insulinoma INS-1 cells. Tagging the granule-resident protein phogrin with a cleavable CLIP tag, we obtain intact fractions of age-distinct granules for proteomic and lipidomic analyses. We find that the lipid composition changes over time, along with the physical properties of the membrane, and that kinesin-1 heavy chain (KIF5b) as well as Ras-related protein 3a (RAB3a) associate preferentially with younger granules. Further, we identify the Rho GTPase-activating protein (ARHGAP1) as a cytosolic factor associated with insulin granules.